Paulus i fångenskap - Lindstedt,Isak (2023)
Paul the Apostle was a very diligent man in many things. Both before his conversion and afterwards he did not cease to work towards his goals; before the conversion eagerly tracking the people believing in Jesus and after his conversion travelling as a missionary, founding churches, writing letters, pursuing his primary target spreading the Gospel. At the same time, he also upheld a regular job. However, when the authorities placed him in captivity the situation changed. He could no longer “go to work”, so to speak. During the pandemic lives took a turn for many employees who had to adapt and find alternate working habits, mainly working from a distance at home or/and connected with colleagues and employer via digital pathways. There has been a debate whether this shift in working mode is good or bad, primarily if the work done from a distance is as effective as being at the regular workplace. This thesis, using Paul’s captivity as a model for working at a distance, examines how the impact of his placement in captivity enhanced or hampered his ability to influence his surroundings, for example by preaching the gospel. By using the method of close reading with comparative perspectives the thesis will show that he did manage to influence his surroundings despite his obvious setback. The thesis first paints a picture of the Roman world of captivity chiefly describing the conditions that faced individuals in prison. Secondly, by exegesis of relevant texts from the captivity epistles, the thesis describes ways in which Paul could affect his surroundings by writing letters and send messengers from captivity. Prayer was also important for Paul in his captivity. Thirdly, exegesis of the captivity epistles proves that even though there were substantial hurdles to Paul’s mission, especially his suffering in chains and his age, Paul still was able to affect his surroundings. He found ways in which he thought he used/was used by the three forms of the Godhead, collaborate with several helpers, and even use a slave for his purpose. He was a trojan horse in the center of Roman power. The thesis even shows that Paul might be best at communicating with his followers at a distance rather working with them up close.